Multi-criteria analysis of alternative tunnel corridors in Göteborg - A geosystem services perspective - Rehman, Abdul (My University, 2024)
The comprehensive plan of Gothenburg’s municipality, Sweden suggests to extend the railway network in the southern part of the city. There exist three potential railway routes, some of which pass through underground tunnels. This report specifically investigates all three tunnel routes, focusing on the subsurface resources. The evaluation is centered on geo-system services along the tunnel corridors, a novel concept that elucidates the resources and services available for human utilization beneath the surface. geo-system services can be categorized into four distinct groups: supporting, cultural, regulating, and provisioning. Initially, an assessment is conducted to evaluate the current quality of these geo-system services and their potential for exploitation. Additionally, any potential conflicts that could have adverse effects on these attributes are examined as part of this evaluation, with Geographic Information Systems (GIS) serving as a key tool in the assessment process. The process utilized for this study is multi-criteria analysis. All three tunnel routes are poised to have a great impact on different geo-system services. The services at high risk are geoenergy wells, groundwater resources, and the mobilizing of pollutants. However, in some parts, the excavation could synergistically extract geo-material through tunnel corridors. But a comparative study is needed to facilitate comprehensive decision-making. Such a study would compare impacts of potential routes on geo-system services. Careful consideration is required to balance extraction benefits against impacts to other underground services and systems. The comparative study aims to support route selection by assessing how alignments may positively or negatively affect the geo-system. This ensures the most suitable choice weighing all relevant factors.
Keywords: Geo-system services; Subsurface; GIS; Multi-criteria analysis